Brian Perry on the roles of livestock in sustainable development - Perry, Brian D. (International Livestock Research Institute, 2007)
Brian Perry marks his final annual planning meeting as a member of ILRI's staff with a series of interviews and a valediction lecture. This includes the changing dynamics of ILRI and her mandate (seminar); the dark shadow of livestock (Hard Talk 1); new infectious plagues of the world (Hard Talk 2); and further globalization of ILRI (Hard Talk 3)